องค์ประกอบภาวะผู้นำที่มีอิทธิพลต่อพฤติกรรม การบริหาร ตามหลักธรรมาภิบาลของผู้บริหาร โรงเรียนประถมศึกษา ในเขตจังหวัดภาคใต้ตอนบน - จินา, สมพงค์ (Asian Journal of Arts and Culture, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์ดังนี้ 1) เพื่อศึกษาองค์ประกอบภาวะผู้นำและพฤติกรรมการบริหารตามหลักธรรมาภิบาลของผู้บริหารโรงเรียนประถมศึกษา ในเขตจังหวัดภาคใต้ตอนบน 2) เพื่อตรวจสอบความสอดคล้องของโมเดลสมการโครงสร้างความสัมพันธ์ระหว่างองค์ประกอบภาวะผู้นำกับพฤติกรรมการบริหารตามหลักธรรมาภิบาลของผู้บริหารโรงเรียน 3) เพื่อตรวจสอบทิศทางของความสัมพันธ์ระหว่างองค์ประกอบภาวะผู้นำกับพฤติกรรมการบริหารตามหลักธรรมาภิบาลของผู้บริหารโรงเรียน กลุ่มตัวอย่างที่ใช้ในการวิจัยคือ ผู้บริหารโรงเรียนประถมศึกษา ในเขตจังหวัดภาคใต้ตอนบน ปีการศึกษา 2556 จำนวน 1,180 คน ได้มาจากวิธีการสุ่มอย่างง่าย (Simple Random Sampling) เครื่องมือที่ใช้ในการวิจัยคือ แบบสอบถาม จำนวน 1ฉบับ มีค่าความเชื่อมั่นรวมทั้งฉบับ เท่ากับ 0.972 วิเคราะห์ข้อมูลโดยใช้สถิติพื้นฐาน วิเคราะห์สมการโครงสร้าง (SEM) โดยใช้โปรแกรม AMOS ผลการวิจัยพบว่า 1) องค์ประกอบภาวะผู้นำของผู้บริหาร ประกอบด้วย องค์ประกอบด้านภูมิหลังของผู้บริหาร สถานการณ์ที่เกี่ยวข้องกับการเป็นผู้นำของผู้บริหาร คุณลักษณะผู้นำของผู้บริหาร พฤติกรรมผู้นำของผู้บริหาร และการใช้ภาวะผู้นำการเปลี่ยนแปลงของผู้บริหาร ส่วนพฤติกรรมการบริหารตามหลักธรรมาภิบาลของผู้บริหาร ประกอบด้วย พฤติกรรมการบริหารตามหลักนิติธรรม หลักคุณธรรม หลักความโปร่งใส หลักความมีส่วนร่วม หลักความรับผิดชอบ และหลักความคุ้มค่า 2) โมเดลสมการโครงสร้างความสัมพันธ์ระหว่างองค์ประกอบภาวะผู้นำกับพฤติกรรมการบริหารตามหลักธรรมาภิบาลของผู้บริหารโรงเรียนประถมศึกษา ในเขตจังหวัดภาคใต้ตอนบน มีความสอดคล้องกับข้อมูลเชิงประจักษ์ 3) ภูมิหลังของผู้บริหาร ไม่มีอิทธิพลทางตรงต่อคุณลักษณะผู้นำของผู้บริหาร พฤติกรรมผู้นำของผู้บริหาร การใช้ภาวะผู้นำการเปลี่ยนแปลงของผู้บริหาร และต่อพฤติกรรมการบริหารตามหลักธรรมาภิบาลของผู้บริหาร 4) สถานการณ์ที่เกี่ยวข้องกับการเป็นผู้นำของผู้บริหารมีอิทธิพลทางตรงต่อคุณลักษณะผู้นำของผู้บริหาร อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.001ต่อพฤติกรรมผู้นำของผู้บริหาร อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.001 ต่อการใช้ภาวะผู้นำการเปลี่ยนแปลงของผู้บริหาร อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.001 และต่อพฤติกรรมการบริหารตามหลักธรรมาภิบาลของผู้บริหาร อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.001 5) คุณลักษณะผู้นำของผู้บริหาร มีอิทธิพลทางตรงต่อพฤติกรรมผู้นำของผู้บริหาร อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.001 ต่อการใช้ภาวะผู้นำการเปลี่ยนแปลงของผู้บริหารอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.01 และต่อพฤติกรรการบริหารตามหลักธรรมาภิบาลของผู้บริหารอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.001 6) พฤติกรรมผู้นำของผู้บริหารไม่มีอิทธิพลทางตรงต่อการใช้ภาวะผู้นำการเปลี่ยนแปลงของผู้บริหาร และต่อพฤติกรรมการบริหารตามหลักธรรมาภิบาลของผู้บริหาร 7) การใช้ภาวะผู้นำการเปลี่ยนแปลงของผู้บริหารมีอิทธิพลทางตรงต่อพฤติกรรมการบริหารตามหลักธรรมาภิบาลของผู้บริหาร อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.001 Leadership Compositions Influencing on Managerial Behaviors of Elementary School Administrators According to Good Governance Principles In the Upper South Region This research had the following objectives : 1) to study the leadership compositions influencing on managerial behaviors of elementary school administrators according to good governance principles in the upper south region, 2) to validate the consistency of the structural equation model of the relationship between leadership compositions and managerial behaviors of school administrators according to good governance principles in the upper south region, and 3) to determine the direction of relationship between leadership compositions and managerial behaviors according to the principles of good governance of school administrators in the upper south region. The samples used in this study, a simple random sampling method, were 1,180 school administrators under the area office of elementary education in the upper south region, in academic year 2013. The instrument used in this study was a set of questionnaires with the total reliability of 0.972. The data were analyzed by using basic statistics, the structural equation model (SEM) analysis wasbusing AMOS programming. The results revealed that : 1) the compositions of administrators’ leadership were included the background of administrators, Situation involving in the leadership of administrators, the leadership traits of administrators, the leadership behaviors of administrators, and the use of transformational leadership of administrators. The managerial behaviors according to the principles of good governance including with managerial behaviors of: rule of law, ethics, transparency, participation, responsibility, and value of money. 2) Structural equation model of relationship between compositions of leadership and managerial behaviors according to the principles of good governance of administrators were consistent with empirical data. 3) The background of administrators were not directly influenced on leadership traits of administrators, leadership behaviors of administrators, the use of transformational leadership of administrators, and managerial behaviors according to the principles of good governance of the management. 4) Situation involving in the leadership of administrators had a directly influenced on leadership traits of administrators at 0.001 level of significance, leadership behaviors of administrators at 0.001 level of significance, the use of transformational leadership of administrators at 0.001 level of significance, and managerial behaviors according to the principles of good governance of the management at 0.001 level of significance. 5) The leadership traits of administrators had directly influenced on leadership behaviors of administrators at 0.001 level of significance, the use of transformational leadership of administrators at 0.01 level of significance, and managerial behaviors according to the principles of good governance of the management at 0.001 level of significance. 6) The leadership behaviors of administrators had no directly influenced on the use of transformational leadership of administrators, and managerial behavior according to the principles of good governance of the management. 7) The use of transformational leadership of administrators had directly influenced on managerial behavior according to the principles of good governance of the management at 0.001 level of significance.